Determinants of neonatal death with emphasis on health care during pregnancy, childbirth and reproductive history - Samir B. Kassar; Ana M.C. Melo; Sônia B. Coutinho; Marilia C. Lima; Pedro I.C. Lira (Elsevier, 2013)
Objective: To identify risk factors for neonatal mortality, focusing on factors related to assistance care during the prenatal period, childbirth, and maternal reproductive history. Methods: This was a case-control study conducted in Maceió, Northeastern Brazil. The sample consisted of 136 cases and 272 controls selected from official Brazilian databases. The cases consisted of all infants who died before 28 days of life, selected from the Mortality Information System, and the controls were survivors during this period, selected from the Information System on Live Births, by random drawing among children born on the same date of the case. Household interviews were conducted with mothers. Results: The logistic regression analysis identified the following as determining factors for death in the neonatal period: mothers with a history of previous children who died in the first year of life (OR = 3.08), hospitalization during pregnancy (OR = 2.48), inadequate prenatal care (OR = 2.49), lack of ultrasound examination during prenatal care (OR = 3.89), transfer of the newborn to another unit after birth (OR = 5.06), admittance of the newborn at the ICU (OR = 5.00), and low birth weight (OR = 2.57). Among the socioeconomic conditions, there was a greater chance for neonatal mortality in homes with fewer residents (OR = 1.73) and with no children younger than five years (OR = 10.10). Conclusion: Several factors that were associated with neonatal mortality in this study may be due to inadequate care during the prenatal period and childbirth, and inadequate newborn care, all of which can be modified. Resumo: Objetivo: Identificar fatores de risco para mortalidade neonatal, com especial atenção aos fatores assistenciais relacionados com os cuidados durante o período pré-natal, parto e história reprodutiva materna. Métodos: Trata-se de um estudo caso-controle realizado em Maceió, Nordeste do Brasil. A amostra consistiu de 136 casos e 272 controles selecionados em bancos de dados oficiais brasileiros. Os casos foram todos os recém-nascidos que morreram antes de completar 28 dias de vida, selecionados no Sistema de Informações sobre Mortalidade, e os controles foram os sobreviventes neste período, selecionados no Sistema de Informações sobre Nascidos Vivos, por sorteio aleatório entre as crianças nascidas na mesma data do caso. Entrevistas domiciliares foram realizadas com as mães. Resultados: A análise de regressão logística identificou como fatores determinantes para a morte no período neonatal mães com história de filhos anteriores que morreram no primeiro ano de vida (OR = 3,08), o internamento durante a gestação (OR = 2,48), o pré-natal inadequado (OR = 2,49), a não realização de ecografia durante o pré-natal (OR = 3,89), a transferência de recém-nascidos para outra unidade após o nascimento (OR = 5,06), os recém-nascidos internados em UTI (OR = 5,00) e o baixo peso ao nascer (OR = 2,57). Entre as condições socioeconômicas, observou-se uma maior chance para mortalidade neonatal em residências com menor número de moradores (OR = 1,73) e com ausência de filhos menores de cinco anos (OR = 10,10). Conclusão: Vários fatores que se mostraram associados à mortalidade neonatal neste estudo podem ser decorrentes de assistência inadequada ao pré-natal, ao parto e ao recém-nascido, sendo, portanto, passíveis de serem modificados. Keywords: Maternal-child health, Neonatal mortality, Risk factors, Case-control studies, Palavras-chave: Saúde materno-infantil, Mortalidade neonatal, Fatores de risco, Estudos caso-controle